Incidental news exposure via social media and political participation: Evidence of reciprocal effects. (January 2022) - Lee, Sangwon; Xenos, Michael
The aim of this study is to investigate the causal direction of the relationship between incidental news exposure via social media and political participation. Unlike prior studies, which have relied on cross-sectional data to examine this link, we used two panel data sets to better identify causal relationships. Specifically, we evaluate two unidirectional models (i.e. mobilization and reinforcement) and a reciprocal causal model using both cross-lagged and autoregressive path models. The findings reveal a more complex relationship than most previous studies have suggested. The relationship between incidental news exposure via social media and political participation appears to be reciprocal, with incidental news exposure and political participation indirectly influencing each other through social media use for political purposes. Furthermore, while the relationship between incidental news exposure and political participation is reciprocal, the participation-to-incidental news exposure path exerted a stronger effect than the reverse path in both studies.